ChemInform Abstract: Peptide δ‐Turn: Literature Survey and Recent Progress. Issue 47 (November 2015) - Toniolo, Claudio; Crisma, Marco; Moretto, Alessandro; Peggion, Cristina; Formaggio, Fernando; Aleman, Carlos; Cativiela, Carlos; Ramakrishnan, Chandrasekharan; Balaram, Padmanabhan
Abstract: Review: 88 refs.